Non-alcoholic Wernicke Encephalopathy in a Young Patient with Adenocarcinoma of the Colon: A Case Report and Review of the Literature - Ziogou, Afroditi; Lymperis, Andreas; Skouteris, Nikolaos; Papageorgiou, Georgios; Charalampakis, Nikolaos (Reviews on Recent Clinical Trials, 2025)
IntroductionWernicke Encephalopathy (W.E.) is an acute neurological disorder induced by thiamine deficiency. Alcohol abuse is considered to be the leading cause of the disease; however, numerous other conditions, such as malnutrition or cancer, have been identified as potential risk factors.Case PresentationClinical manifestations include a typical triad of mental status alteration, nystagmus, and ataxia and are attributed to damage in brain regions of high thiamine demand. The diagnosis is mainly clinical and further supported by the immediate response of neurological signs to parenteral thiamine administration. Among paraclinical examinations, brain MRI is considered substantial for diagnosis and is supported by the determination of thiamine blood levels.ConclusionNon-alcoholic W.E. is trickier to diagnose due to its atypical clinical course and risk factors. We herein describe a case of non-alcoholic W.E. in a woman with colon cancer who gradually developed the classic symptoms of thiamine deficiency.
Keywords: cancer